Fluorescence-Guided Surgery for High-Grade Gliomas: State of the Art and New Perspectives. (1st July 2021) - Palmieri, Giuseppe; Cofano, Fabio; Salvati, Luca Francesco; Monticelli, Matteo; Zeppa, Pietro; Perna, Giuseppe Di; Melcarne, Antonio; Altieri, Roberto; La Rocca, Giuseppe; Sabatino, Giovanni; Barbagallo, Giuseppe Maria; Tartara, Fulvio; et al.
High-grade gliomas are aggressive tumors that require multimodal management and gross total resection is considered to be the first crucial step of treatment. Because of their infiltrative nature, intraoperative differentiation of neoplastic tissue from normal parenchyma can be challenging. For these reasons, in the recent years, neurosurgeons have increasingly performed this surgery under the guidance of tissue fluorescence. Sodium fluoresceine and 5-aminolevulinic acid represent the 2 main compounds that allow real-time identification of residual malignant tissue and have been associated with improved gross total resection and radiological outcomes. Though presenting different profiles of sensitivity and specificity and further investigations concerning cost-effectiveness are need, Sodium fluoresceine, 5-aminolevulinic acid and new phluorophores, such as Indocyanine green, represent some of the most important tools in the neurosurgeon's hands to achieve gross total resection.